Prediction of designer drugs: Synthesis and spectroscopic analysis of synthetic cathinone analogs that may appear on the Swedish drug market. Issue 7 (30th March 2018) - Carlsson, Andreas; Sandgren, Veronica; Svensson, Stefan; Konradsson, Peter; Dunne, Simon; Josefsson, Martin; Dahlén, Johan
Abstract: The use of hyphenated analytical techniques in forensic drug screening enables simultaneous identification of a wide range of different compounds. However, the appearance of drug seizures containing new substances, mainly new psychoactive substances (NPS), is steadily increasing. These new and other already known substances often possess structural similarities and consequently they exhibit spectral data with slight differences. This situation has made the criteria that ensure indubitable identification of compounds increasingly important. In this work, 6 new synthetic cathinones that have not yet appeared in any Swedish drug seizures were synthesized. Their chemical structures were similar to those of already known cathinone analogs of which 42 were also included in the study. Hence, a total of 48 synthetic cathinones making up sets of homologous and regioisomeric compounds were used to challenge the capabilities of various analytical techniques commonly applied in forensic drug screening, ie, gas chromatography–mass spectrometry (GC–MS), gas chromatography–Fourier transform infrared spectroscopy (GC–FTIR), nuclear magnetic resonance (NMR), and liquid chromatography quadrupole time‐of‐flight mass spectrometry (LC–QTOF–MS). Special attention was paid to the capabilities of GC–MS and GC–FTIR to distinguish between the synthetic cathinones and the results showed that neither GC–MS nor GC–FTIR alone can successfully differentiate between all synthetic cathinones. However, the 2 techniques proved to be complementary and their combined use is therefore beneficial. For example, the structural homologs were better differentiated by GC–MS, while GC–FTIR performed better for the regioisomers. Further, new spectroscopic data of the synthesized cathinone analogs is hereby presented for the forensic community. The synthetic work also showed that cathinone reference compounds can be produced in few reaction steps. Abstract : This work contains synthesis and spectroscopic comparisons of synthetic cathinone analogues and addresses in particular the differentiation of such new psychoactive substances (NPS) by gas chromatography mass spectrometry (GC‐MS) and gas chromatography Fourier transform infrared spectroscopy (GC‐FTIR).